Mortality of TB-HIV Co-Infection Patients Based on CD4 Level: Meta-Analysis - Victoria Husadani Permata Sari; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Tuberculosis (TB) is the most common cause of death in patients with the Human Immunodeficiency Virus (HIV). Understanding CD4 as a predictor of mortality from TBHIV coinfection is critical to improving disease management and minimizing mortality. This study aims to examine the mortality risk of TBHIV-coinfected patients based on CD4 values.Subjects and Method: Metaanalysis was performed according to the PRISMA flow chart and the PICO model (Population: TBHIV coinfected patients, Intervention: CD4 value <200 cells/µL, Comparison: CD4≥200 cells/µL, Outcome: mortality). The databases used are Google Scholar, PubMed, Scopus, Proquest, and Science Direct. Keywords used (coinfection OR